Corporate governance and banking performance: the mediating role of intellectual capital among OIC countries - Aslam, Ejaz; Haron, Razali (Emerald Publishing Limited, 2020)
Purpose–The existing literature asserted that the Islamic banking industry progress significantly, but it has increasingly found asset deficient which assaulted the performance of Islamic banks (IBs). The aim of this study to examine the mediating role of intellectual capital (IC) on the relationship between corporate governance (CG) mechanisms and IBs performance is examined (ATO, NPM). Design/methodology/approach-A panel sample of 129 IBs is drawn from the 29 organisation of Islamic cooperation (OIC) countries from 2008 to 2017. Two-step system generalized method of moments (2SYS-GMM) was used to account for the unobserved endogeneity and heteroscedasticity problem. Findings– The empirical findings demonstrate that there is a significant impact of the CG mechanism on IC. Moreover, the empirical findings indicate that CG has a direct influence on banking performance but it affects indirectly through IC. IC also appears to have a mediation role in the relationship between the CG mechanism and the performance of IBs. Research limitations/implications– As the empirical research on IC from CG point of view in Islamic banking is generally new in the banking literature, the output of this research will contribute to the building up of empirical framework and practices regarding IC in the Islamic banking industry by using the resource-based theory as a leading theory and agency theory as a sub theory. It is anticipated that this study provided a superior comprehensive discussion of the IC in IBs across OIC countries which discovers theCGmechanism to influence the IC to improve banking performance. Practical implications–This study offers useful insights to the regulators and practitioners to draw the rules and regulations in improving the CG mechanism and the effectiveness of internal controls by acknowledging the importance of IC in Islamic banking institutions. Particularly, the findings of this study may be of benefit to bankers to efficiently use the IC as a premise to design new and creative strategies to achieve a competitive advantage in the banking industry. Originality/value–The study is unique in its nature because it presents a successful model for IBs to concentrate more on the role of IC in enhancing banking performance, which might be used by the banks to rearrange the roles within CG, to place their priorities regarding the internal governance system and financial plans for competency enhancement.